Morphological characterization of amoebas involved in a nodular gill disease (NGD) outbreak in brook trout (Salvelinus fontinalis) and rainbow trout (Oncorhynchus mykiss) farmed in Northern Italy. - Brocca G.; Perolo A.; Gustinelli A.; Fioravanti M. L.; Dykova I.; Quaglio F. (Goldgrafic Napoli, 2022)
INTRODUCTION: Nodular Gill Disease (NGD) is an emerging amoebic disease of freshwater salmonids farmed worldwide. Although it is more frequently described in rainbow trout (Oncorhynchus mykiss), other co-farmed salmonids may be affected, including arctic char (Salvelinus alpinus), Chinook salmon (Oncorhynchus tshawytscha), and brown trout (Salmo trutta). An outbreak of nGd-related mortality and morphological characterization of involved amoebas is here described in brook trout (Salvelinus fontinalis) farmed in northern Italy. MATERIALS AND METHODS: The NGD outbreak was monitored in a mixed rainbow/brook trout facility. The mortality reached 30% for brook trout over a 1-month period. Twenty brook trout and twenty rainbow trout presenting clinical signs of NGD were sampled and underwent macroscopic, microscopic, and histological examination with the use of Giemsa stain, with the assessment of 6-grade lesion scores. From the same facility a second sample was carried out after few weeks collecting 2-3 portions of gill arches from 50 rainbow trout. Gills were put on non-nutrient agar (NNA) Petri dishes for amoeba isolation, cultivation, and identification by Transmission Electron Microscopy (TEM). RESULTS AND CONCLUSIONS: brook trout showed macroscopic and histological lesions classically associated with NGD. When compared with affected rainbow trout, affected brook trout presented milder amoebic infection associated with larger size and higher severity of the lesions. Successful amoeba cultivation was possible from 2 samples, resulting in the isolation of 2 amoeba colonies. The first colony was composed of motionless rounded or ovoid cells (8-10 µm) with filopods. The second colony was made of actively motile irregularly shaped cells (10-15 µm). When observed with TEM, the cells of the first colony showed an organic case covering the whole cell surface with the presence of a pseudostoma, while in the cells of the second colony the outer plasma membrane was covered by a glycocalyx. They were morphologically ...